LOCAL GOVERNANCE ACTIVITIES IN SUPPORTING FISHERIES AND TOURISM OF THE SZCZECIN BAY - Jolanta Zieziula; Agnieszka Malkowska; Piotr Nowaczyk (Acta Scientiarum Polonorum. Oeconomia, 2011)
Communes located by the Szczecin Bay have insufficiently supported fisheries and tourism in spite of being provided with good conditions for their development. The results of questionnaires and surveys held in 2008–2010 indicate that local self-governments gradually communalized fishing ports and offered advisory support for fisherman. Additionally, they showed a flexible approach towards the adjustment of rental fees for port utilities as well as property taxes. The lack of support or its being insufficient resulted partly from inadequate knowledge of problems by local authorities and partly because of the lack of financial resources for maintaining ports, implementing the indispensable infrastructural investments as well as meeting other needs for development. In 2009, the Maritime Office started transferring to local authorities tax fees on estates located under the waters of the Szczecin Bay. The financial situation of the local communities has been essentially improved. With the provided financial means, local authorities were able to prepare and pre-finance projects allowing them to apply for the EU co-financing of infrastructural development projects and other needs connected with tourism and fisheries.